2013
DOI: 10.17303/jce.2014.105
|View full text |Cite
|
Sign up to set email alerts
|

Review on Dye Removal from Its Aqueous Solution into Alternative Cost Effective and Non-Conventional Adsorbents

Abstract: Dyes are complex organic compounds which are used by various industries to colour their products. These dyes are purged from various industrial sources such as textile, cosmetic, paper, leather, rubber and printing industries. Wastewater effluents contain dyes which may cause potential hazards to the environment. Some of these dyes are toxic, carcinogenic and can cause skin and eye irritation. Therefore, many researchers have been studied the effectiveness of dyes removal from aqueous solution by different sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 97 publications
1
14
0
1
Order By: Relevance
“…When these organic dyes are discharged into water resources, they can be very harmful. [22][23][24][25] Malachite Green (MG), a watersoluble cationic dye used as an antifungal, antimicrobial and a topical antiseptic in aquaculture since 1930, 26,27 has a structure similar to carcinogenic triphenylmethane dyes. Besides, the effluent containing Cr(VI) ions, the inorganic heavy metal water pollutant, is very toxic and detrimental to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…When these organic dyes are discharged into water resources, they can be very harmful. [22][23][24][25] Malachite Green (MG), a watersoluble cationic dye used as an antifungal, antimicrobial and a topical antiseptic in aquaculture since 1930, 26,27 has a structure similar to carcinogenic triphenylmethane dyes. Besides, the effluent containing Cr(VI) ions, the inorganic heavy metal water pollutant, is very toxic and detrimental to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of initial dye concentration (5-30 mg/L) on adsorption of BPB was studied by mixing 300 mg of FBP in a 250 ml flask containing 100 ml of the desired dye solution at room temperature and agitated at 200 rpm for 1 h [34,47]. The dye solution was then decanted and centrifuged at 1,500 rpm for 30 min and the absorbance of the supernatant was then analysed using a UV-Vis spectrophotometer at 590 nm [46].…”
Section: Effect Of Initial Dye Concentrationmentioning
confidence: 99%
“…Sorbent dosage evaluation showed that higher values for the adsorption capacity were achieved with a lower amount of adsorbent -0.5 g. The removal efficiencies obtained at the equilibrium state per adsorbent weight for RB were: 50.21% (0.5 g) and 85.48% (1.0 g); for RR: 58.86% (0.5 g) and 81.00% (1.0 g). The short time necessary to achieve the equilibrium state (below 5 min) is characteristic of the monolayer physisorption process, in which the adsorbate binds to the adsorbent surface through weak intermolecular interactions such as van der Waals forces, hydrophobicity, hydrogen bonding, polarity, static interactions, dipole-dipole interactions and π-π interactions (Ruthven 1984;Sen & Dawood 2014;Scheufele et al 2016). The pseudo-second-order model best fit the experimental data, with a good coefficient of determination (R 2 ) for both dyes.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Moreover, dye consumption has continually increased over the years, not just in the textile industry, but also in rubber, plastic, leather, paper, cosmetic, pharmaceutical and food industries (Rani et al 2017). Total dye consumption in the textile industry worldwide is more than 10,000 tons per year and about 10-15% of this amount is discharged as wastewater during the dyeing processes (Gupta et al 2013;Sen & Dawood 2014). Dyes can be classified as a function of the charge in reactive, anionic, cationic and non-ionic compounds; among them, the reactive azo dyes are those most commonly used by the textile industry, which is a major concern due to their anaerobic degradation process, which releases toxic aromatic amines (Aguiar et al 2017).…”
Section: Introductionmentioning
confidence: 99%